2016
DOI: 10.4172/2167-7956.1000143
|View full text |Cite
|
Sign up to set email alerts
|

Psychostimulants, Brain Membrane Lipids and Dopamine Transmission

Abstract: Membrane lipids in the brain play important roles in regulation of the membrane compartmentalization, function and signaling of neurotransmitter transporters and receptors. This review summarizes findings on changes in the composition and metabolism of brain membrane lipids such as phospholipids, cholesterol and sphingolipids following chronic exposure to psychostimulants. We also discussed the mechanisms by which membrane lipids regulate the membrane compartmentalization and function of dopamine transports an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…This observation suggests that SMA is a suitable new alternative for membrane protein purification enabling the study of the different GPCR signalling pathways in a more native environment than the detergent setting. To emphasise how crucial the protein-lipid environment is for ligand binding or protein signalling, it has been demonstrated that dopamine receptors, upon interaction with certain drugs such as cocaine, are able to translocate to a different lipid environment [60,61]. Thus, the ability to directly extract proteins in their preferred local lipid composition using SMA Lipodisqs may offer significant advantages over current approaches.…”
Section: Radio-ligand Binding Assaysmentioning
confidence: 99%
“…This observation suggests that SMA is a suitable new alternative for membrane protein purification enabling the study of the different GPCR signalling pathways in a more native environment than the detergent setting. To emphasise how crucial the protein-lipid environment is for ligand binding or protein signalling, it has been demonstrated that dopamine receptors, upon interaction with certain drugs such as cocaine, are able to translocate to a different lipid environment [60,61]. Thus, the ability to directly extract proteins in their preferred local lipid composition using SMA Lipodisqs may offer significant advantages over current approaches.…”
Section: Radio-ligand Binding Assaysmentioning
confidence: 99%
“…Concerning dopamine neurotransmission, using super-resolution microscopy, it has been shown that the dopaminergic transporter (DAT) may be sequestrated in cholesterol-dependent nanodomains in the membrane of presynaptic neurons and that cholesterol depletion reduces localization of the DAT in these nanodomains (Rahbek-Clemmensen et al, 2017). Other evidences suggest that cholesterol dysregulation may alter the DAT functioning (Jones et al, 2012; Luessen and Chen, 2016; Zeppelin et al, 2018). Thus, it is possible that if cholesterol homeostasis is dysregulated, the functioning of the dopamine system and eventually the response to future exposure to drugs may be changed, which may in turn increase the risks of addiction.…”
Section: Discussionmentioning
confidence: 99%